Reading Speed of PBSI Students of UIN Syarif Hidayatullah Jakarta - Elvi Susanti (Masyarakat Linguistik Indonesia Universitas Andalas, 2019)
This study uses the qualitative descriptive method, which is by describing the data obtained from UIN students. The population of this study was all PBSI (Pendidikan Bahasa dan Sastra Indonesia) students who attended Reading Skills courses. The researcher took a sample of research from the 4A and 4B semester students of the 2016/2017 academic year with a total of 76 people. The results showed that there were still many PBSI UIN students who had low reading speed. The results of KPM/SPM (kecepatan per menit/reading speed per minute) which must be at least 325 kpm, are only achieved by one student or only 1.3% of 2 classes with total 76 people. The reason is that they only read once a week, just read books related to college assignments, get distractions while reading, difficulties in understanding foreign terms and languages, etc.